THE INFLUENCE OF LINGUISTIC FACTORS IN PAST TENSE FORMS - Sobirova Muzayyana Ilhomjon qizi (Western European Studies, 2024)
in this article, opinions on the role of linguistic factors in the speech use of past tense forms of the verb are presented, and conclusions on the solution of the problem are presented.
Keywords: moment of speech; lexeme composition; morphological form